Unusual presentation of cat scratch disease: case report - AKKOÇ, GÜLŞEN; DİZİ IŞIK, AYLİN; CANİZCİ ERDEMLİ, PINAR; PARLAK, BURCU; YAPICI, ÖZGE; ÇELİKEL, ÇİĞDEM; ÖCAL DEMİR, SEVLİYA (My University, 2024)
Cat scratch disease (CSD) is an infection caused by Bartonella henselae, presents with non-specific symptoms like lymphadenopathy, fever, and fatigue. It can progress to disseminated disease, leading to complications such as liver and splenic micro abscesses, osteomyelitis, encephalitis, and uveitis. Diagnosis is challenging due to varied presentations and limited tests. Treatment involves supportive care, with severe cases requiring antimicrobial therapy. In this report, we present a case of Cat scratch disease characterized by an atypical clinical manifestation, hepatosplenic and paravertebral involvement.
Keywords: Tıp; Mikrobiyoloji ve Klinik Mikrobiyoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Microbiology and Clinical Microbiology; Life Sciences; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); İmmünoloji; Mikrobiyoloji; BULAŞICI HASTALIKLAR; MİKROBİYOLOJİ; Life Sciences (LIFE); IMMUNOLOGY; MICROBIOLOGY; INFECTIOUS DISEASES; Mikrobiyoloji (tıbbi); Bulaşıcı hastalıklar; Microbiology (medical); Infectious Diseases; Disseminated; Lymphadenopathy; Osteomyelitis; Scratch